ANALYSIS OF THE INFLUENCE OF NUTRITION ON THE FREQUENCY OF GASTRITIS IN STUDENTS OF TASHKENT - Jalolov N. N.; Niyazova O. A. (Journals Park Publishing, 2024)
This article is devoted to the identification and analysis of factors that contribute to the manifestation of such a disease as gastritis in the student sphere of life. After the survey, the main factors contributing to the development of gastritis in students were identified.
Keywords: Nutrition, students, gastritis, fast food.